PENDIDIKAN DAN EFISIENSI: METODE DATA ENVELOPMENT ANALYSIS (Education and Efficiency: Data Envelopment Analysis Methode) (JURNAL PERSPEKTIF BISNIS, 2013)
The purpose of this research is to measure technical efficiency on Departements in University of Lampung periode 2009. Data were analyzed using Data Envelopment Analysis (DEA) model CRS and VRS input oriented. The input variables are percent of doctor, average educationâs cost, and number of student. The output variable is average GPA. The results show that DMU 11 and DMU 17 was the best practise for CRS and VRS model. Based on CRS model, there are two best practiceâs. On the other hand, based on VRS model there are six best practiceâs. In general, basen on CRS model the technical efficiency in Departements are low. It is indicated that technical efficiency scores of the majority of the Departements are below average score in year of observation.Â Keywords: Technical efficiency, education